ANALISIS LITERASI KEUANGAN, PERSYARATAN PEMBIAYAAN DAN KEBERLANGSUNGAN USAHA TERHADAP KEMUDAHAN AKSES PEMBIAYAAN FORMAL PADA UMKM - Nampi Warih Ningsih; Ida Aryati; Rochmi Widayanti (JURNAL ILMIAH EDUNOMIKA, 2019)
Economic development in Indonesian is currently growing, one of the factors that drives it is growth is UMKM. Because capital that is not large can open up employment opportunities for them selves or even for others to improve their families standard of living. Knowledge of financial literacy requirements and get access to formal financing for business continuty. Study research uses a descriptive quantitative approach. Questionnaires was used to obtain data from PNM Mekaar Banjarsar. Samples is the study uses 150 respondens and the time needed in this study was more or less for 3 months. The results of the study show that financial literacy, finansing requirements and business contunity to facilitate acces to formal financing at UMKM. KeyWord : Literacy Financial, Financing Requirements, Business Continuty, Financial Access to Financial, UMKM